Super-hydrophobic coating with excellent mechanical property and preparation method thereof
Through layered spraying technology, combined with fluoroboration modified phenolic resin and micro-nano structure particles, a superhydrophobic coating with a double-layer composite structure is formed, which solves the problem of poor mechanical stability of the existing coating and achieves both excellent mechanical properties and superhydrophobic properties.
Patent Information
- Application Number
- CN202411690460.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing superhydrophobic coating has poor mechanical stability, which restricts its practical application.
Using layered spraying technology, the base coating contains fluoroborated modified phenolic resin, phenolic resin and micro-nano structural particles, and the surface coating contains fluoroborated modified phenolic resin, phenolic resin and hydrophobic modified micro-nano structural particles. The composition and proportion of the micro-nano structural particles are adjusted to form a double-layer composite structure.
It improves the mechanical properties and mechanical stability of the superhydrophobic coating, enhances the wear resistance and corrosion resistance of the coating, and maintains good superhydrophobic properties.
Smart Images

Figure CN119662086A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrophobic coatings, and in particular relates to a super hydrophobic coating with excellent mechanical properties and a preparation method thereof. Background Art
[0002] Super-hydrophobicity refers to the phenomenon that the contact angle of a water droplet stationary on the surface of an object is greater than 150° and the rolling angle is less than 10°. Super-hydrophobic surfaces have good application prospects in the fields of corrosion protection, self-cleaning, anti-icing, and directional liquid transportation. Commonly used methods for preparing super-hydrophobic coatings include electrochemical deposition, template method, sol-gel method, etching method, self-assembly method, etc. Most of these preparation methods are complex in process, cumbersome in procedures, and the coating has poor resistance to mechanical wear. The problem of poor mechanical stability of super-hydrophobic coatings has become a key problem restricting its practical application.
[0003] Existing methods for optimizing the surface mechanical properties of super-hydrophobic coatings often have a negative impact on their super-hydrophobic properties, and the process is complex and costly. It is of great practical significance to seek simple, easy and low-cost methods that will not have a negative impact on the wetting properties of super-hydrophobic coatings and can improve the mechanical stability of the coating. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a super-hydrophobic coating with excellent mechanical properties and a preparation method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A super-hydrophobic coating with excellent mechanical properties, comprising a bottom layer and a surface layer arranged in sequence from bottom to top, wherein the bottom layer raw materials comprise fluorinated boron modified phenolic resin, phenolic resin and micro-nano structure particles, and the surface layer raw materials comprise fluorinated boron modified phenolic resin, phenolic resin and hydrophobically modified micro-nano structure particles;
[0008] The mass ratio of the micro-nano structure particles in the bottom layer to the hydrophobically modified micro-nano structure particles in the surface layer is (0.2-0.6):1.
[0009] The second technical solution of the present invention:
[0010] A method for preparing a super-hydrophobic coating with excellent mechanical properties comprises the following steps: spraying a bottom coating and a top coating on a substrate surface in sequence by layered spraying, forming a bottom layer and a top layer on the substrate surface in sequence, and drying and curing to obtain the super-hydrophobic coating with excellent mechanical properties;
[0011] The primer is prepared by using a fluorine-containing boron-modified phenolic resin and a phenolic resin mixture as the main body, embedding micro-nano structure particles, and dispersing them in a solvent;
[0012] The surface coating is prepared by taking fluorine-containing boronized modified phenolic resin and a phenolic resin mixture as the main body, embedding hydrophobic modified micro-nano structure particles, and dispersing them in a solvent.
[0013] Furthermore, in the primer, the micro-nano structured particles include one or more of hydroxylated multi-walled carbon nanotubes and nanocellulose, and the role of such micro-nano structured particles is to be dispersed in the resin to enhance the mechanical properties of the resin base. The mass ratio of the fluorine-containing boron modified phenolic resin to the phenolic resin is 1: (2.5-3.5), and the mass ratio of the micro-nano structured particles to the fluorine-containing boron modified phenolic resin is 2: 5.
[0014] Furthermore, in the surface coating, the hydrophobically modified micro-nano structure particles include one or more of ZrO2, SiO2, Al2O3, TiO2, hydroxylated multi-walled carbon nanotubes, nanocellulose, Fe3O4, Fe2O3 and ZnO modified with fluorinated siloxane, and the role of such hydrophobically modified micro-nano structure particles is to be dispersed in the resin, construct micro-nano composite structures of different levels, and enhance the hydrophobic properties of the coating. The mass ratio of the fluorinated boron modified phenolic resin to the phenolic resin is 1: (2.5-3.5), and the mass ratio of the hydrophobically modified micro-nano structure particles to the fluorinated boron modified phenolic resin is 7: 5.
[0015] Furthermore, the fluorine-containing siloxane is 1H,1H,2H,2H-perfluorodecyltriethoxysilane.
[0016] Furthermore, the preparation method of the hydrophobically modified micro-nano structure particles comprises the following steps:
[0017] Adding micro-nano structure particles and 1H,1H,2H,2H-perfluorodecyltriethoxysilane to a solvent (anhydrous ethanol or acetone), adding ammonia water, and stirring at 30° C. for 0.5 to 3 hours to obtain the hydrophobically modified micro-nano structure particles;
[0018] Among them, the volume ratio of ammonia water to solvent is 1: (3-5), the volume ratio of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to solvent is 1: (100-150), and the mass ratio of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to micro-nanostructure particles is 1: (0.1-1).
[0019] Furthermore, the solvents used in the base coating and the surface coating are both anhydrous ethanol or acetone.
[0020] Furthermore, the method specifically includes the following steps:
[0021] (1) grinding, polishing and ultrasonic cleaning the surface of the substrate;
[0022] (2) Mix the micro-nanostructure particles, solvent (anhydrous ethanol or acetone) and ammonia water, and stir them magnetically at 30°C for 1 hour, which is referred to as solution A. Add the boron-modified phenolic resin, phenolic resin, silane coupling agent, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane to the solvent (anhydrous ethanol or acetone), and stir them magnetically at 30°C for 1 hour, which is referred to as solution B. Pour solution A into solution B, and stir them magnetically at 30°C for 1 to 2 hours to obtain a primer.
[0023] Add the micro-nano structure particles and 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane to a solvent (anhydrous ethanol or acetone), add ammonia water, and stir magnetically in a water bath at 30°C for 0.5 to 3 hours to obtain a hydrophobically modified micro-nano structure particle emulsion, which is recorded as solution C. Add the boronized modified phenolic resin, phenolic resin, and silane coupling agent to the solvent (anhydrous ethanol or acetone), stir magnetically in a water bath at 30°C for 30 minutes, then add 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane, stir magnetically in a water bath at 30°C for 30 minutes, which is recorded as solution D. Pour solution C into solution D, stir magnetically at 30°C for 1 hour, and obtain a surface coating.
[0024] (3) first spraying the base coating on the surface of the substrate obtained in step (1), drying until the base coating forms a semi-cured layer, then spraying the top coating, and continuing to dry until the top coating is completely cured to obtain the super hydrophobic coating with excellent mechanical properties.
[0025] Furthermore, in step (1), the substrate includes metal and non-metal materials such as aluminum alloy, magnesium alloy, carbon steel, stainless steel, glass, ceramics, etc.
[0026] Furthermore, in step (1), the polishing treatment is performed by polishing with SiC sandpaper, and the particle sizes of the sandpaper are 100, 400, 600, 800, 1000, and 1500 meshes respectively; and the ultrasonic cleaning treatment is performed by ultrasonic cleaning in deionized water, anhydrous ethanol, and acetone for 15 minutes respectively.
[0027] Furthermore, in step (2), the temperature of the water bath heating and stirring is 30° C., and the time is 0.5 to 3 hours.
[0028] Furthermore, in step (3), the spraying flow rate of the spray gun is 0.1-1 mL / s, the spray gun sprays at a distance of 10-30 cm from the substrate, the spray gun pressure is 0.2-1 MPa, and the spray gun movement speed is 2 cm / s.
[0029] Furthermore, in step (3), the bottom layer is dried at 130° C. to 150° C. for 3 to 5 minutes to form a semi-cured layer.
[0030] Furthermore, in step (3), drying is performed at 150° C. for 1 to 3 hours until the surface layer is completely solidified.
[0031] Compared with the prior art, the present invention has the following advantages and technical effects:
[0032] (1) The present invention mixes a boron-modified phenolic resin with a phenolic resin and adopts a layered spraying method to obtain a super-hydrophobic coating with a double-layer composite structure. According to the different performance requirements of the bottom layer and the surface layer, the composition and proportion of the micro-nano structure particles in the coating are adjusted, and the polymer filler wraps the micro-nano structure particles with different concentration gradients, thereby protecting the ability of the micro-nano structure to resist mechanical wear and can greatly improve the stability of the mechanical properties, thereby obtaining a super-hydrophobic coating with good mechanical properties.
[0033] (2) The super-hydrophobic coating prepared by the present invention has good mechanical stability and bonding strength, which is beneficial to improving the durability, corrosion resistance, and acid and alkali resistance of the substrate under some complex working conditions.
[0034] (3) The preparation method of the present invention is simple and easy to implement, with low cost. It improves the mechanical stability of the coating without causing a negative impact on the wettability of the coating. Compared with most other existing methods, the preparation method is simple, the reagents involved are cheap, the preparation cycle is short, the temperature requirement is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0036] Figure 1 Schematic diagram of the process flow of the super-hydrophobic coating with excellent mechanical properties of the present invention;
[0037] Figure 2 Schematic diagram of the preparation process of P-U75V-FS in Example 1 of the present invention (a) and schematic diagram of the hydrophobic modification of the hydrophobically modified micro-nanostructure particles in step (2) (b);
[0038] Figure 3 This is a scanning electron microscope (SEM) image of P-U75V-FS prepared in Example 1 of the present invention;
[0039] Figure 4 The static contact angle diagram of the water droplet and the surface of the super-hydrophobic coating prepared in Examples 1-3 of the present invention;
[0040] Figure 5 The static contact angle diagram of the water droplet and the surface after the wear test of the super-hydrophobic coating prepared in Examples 1-3 of the present invention;
[0041] Figure 6 The Tafel curves of the super-hydrophobic coating prepared in Examples 1-3 and untreated carbon steel U75V;
[0042] Figure 7 The static contact angle diagrams of the water droplets and the surfaces of the coatings prepared in Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0044] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0045] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0048] The embodiment of the present invention provides a super-hydrophobic coating with excellent mechanical properties, comprising a bottom layer and a surface layer arranged in sequence from bottom to top, wherein the bottom layer raw material comprises fluorinated boron modified phenolic resin, phenolic resin and micro-nano structure particles, and the surface layer raw material comprises fluorinated boron modified phenolic resin, phenolic resin and hydrophobically modified micro-nano structure particles;
[0049] The mass ratio of the micro-nano structure particles in the bottom layer to the hydrophobically modified micro-nano structure particles in the surface layer is (0.2-0.6):1.
[0050] The embodiment of the present invention also provides a method for preparing a super-hydrophobic coating with excellent mechanical properties, comprising the following steps: spraying a base coating and a top coating on the surface of a substrate in a layered spraying manner, forming a base layer and a top layer on the surface of the substrate in sequence, and drying and curing to obtain the super-hydrophobic coating with excellent mechanical properties;
[0051] The primer is prepared by using a fluorine-containing boron-modified phenolic resin and a phenolic resin mixture as the main body, embedding micro-nano structure particles, and dispersing them in a solvent;
[0052] The surface coating is prepared by taking fluorine-containing boronized modified phenolic resin and a phenolic resin mixture as the main body, embedding hydrophobic modified micro-nano structure particles, and dispersing them in a solvent.
[0053] In a preferred embodiment of the present invention, in the primer, the micro-nanostructured particles include one or more of hydroxylated multi-walled carbon nanotubes and nanocellulose, the particle size of the micro-nanostructured particles is ≤25 μm, the mass ratio of the fluorine-borated modified phenolic resin to the phenolic resin is 1:(2.5~3.5), and the mass ratio of the micro-nanostructured particles to the fluorine-borated modified phenolic resin is 2:5.
[0054] In a preferred embodiment of the present invention, in the surface coating, the hydrophobically modified micro-nanostructured particles include one or more of ZrO2, SiO2, Al2O3, TiO2, hydroxylated multi-walled carbon nanotubes, cellulose, Fe3O4, Fe2O3 and ZnO modified with fluorinated siloxane, the particle size of the hydrophobically modified micro-nanostructured particles is 20 nm, the mass ratio of the fluorinated boron-modified phenolic resin to the phenolic resin is 1:(2.5-3.5), and the mass ratio of the hydrophobically modified micro-nanostructured particles to the fluorinated boron-modified phenolic resin is 7:5.
[0055] In a preferred embodiment of the present invention, the fluorine-containing siloxane is 1H,1H,2H,2H-perfluorodecyltriethoxysilane.
[0056] In a preferred embodiment of the present invention, the method for preparing the hydrophobically modified micro-nanostructure particles comprises the following steps:
[0057] Adding micro-nano structure particles and 1H,1H,2H,2H-perfluorodecyltriethoxysilane to a solvent (anhydrous ethanol or acetone), adding ammonia water, and stirring at 30° C. for 0.5 to 3 hours to obtain the hydrophobically modified micro-nano structure particles;
[0058] Among them, the volume ratio of ammonia water to solvent is 1: (3-5), the volume ratio of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to solvent is 1: (100-150), and the mass ratio of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to micro-nanostructure particles is 1: (0.1-1).
[0059] In a preferred embodiment of the present invention, the solvents used in the base coating and the surface coating are both anhydrous ethanol or acetone.
[0060] In a preferred embodiment of the present invention, the following steps are specifically included:
[0061] (1) grinding, polishing and ultrasonic cleaning the substrate surface;
[0062] (2) Mix the micro-nanostructure particles, solvent (anhydrous ethanol or acetone) and ammonia water, and stir them magnetically at 30°C for 1 hour, which is referred to as solution A. Add the boron-modified phenolic resin, phenolic resin, silane coupling agent, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane to the solvent (anhydrous ethanol or acetone), and stir them magnetically at 30°C for 1 hour, which is referred to as solution B. Pour solution A into solution B, and stir them magnetically at 30°C for 1 to 2 hours to obtain a primer.
[0063] Add the micro-nano structure particles and 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane to a solvent (anhydrous ethanol or acetone), add ammonia water, and stir magnetically at 30°C for 0.5 to 3 hours to obtain a hydrophobically modified micro-nano structure particle emulsion, which is recorded as solution C. Add the boronized modified phenolic resin, phenolic resin, and silane coupling agent to the solvent (anhydrous ethanol or acetone), stir magnetically at 30°C for 30 minutes, then add 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane, stir magnetically at 30°C for 30 minutes, which is recorded as solution D. Pour solution C into solution D, stir magnetically at 30°C for 1 hour, and obtain a surface coating.
[0064] (3) first spraying the base coating on the surface of the substrate obtained in step (1), drying until the base coating forms a semi-cured layer, then spraying the top coating, and continuing to dry until the top coating is completely cured to obtain the super hydrophobic coating with excellent mechanical properties.
[0065] The process flow diagram of the super hydrophobic coating with excellent mechanical properties of the present invention is shown in Figure 1 .
[0066] In a preferred embodiment of the present invention, in step (1), the substrate includes metal and non-metal materials such as aluminum alloy, magnesium alloy, carbon steel, stainless steel, glass, ceramics, etc.
[0067] In a preferred embodiment of the present invention, in step (1), the polishing treatment is performed by polishing with SiC sandpaper, and the particle sizes of the sandpaper are 100, 400, 600, 800, 1000, and 1500 meshes, respectively; and the ultrasonic cleaning treatment is performed by ultrasonic cleaning in deionized water, anhydrous ethanol, and acetone, respectively, for 15 minutes.
[0068] In a preferred embodiment of the present invention, in step (2), the temperature of the water bath heating and stirring is 30° C., and the time is 0.5 to 3 hours.
[0069] In a preferred embodiment of the present invention, in step (3), the spraying flow rate of the spray gun is 0.1-1 mL / s, the spray gun sprays at a distance of 10-30 cm from the substrate, the spray gun pressure is 0.2-1 MPa, and the spray gun movement speed is 2 cm / s.
[0070] In a preferred embodiment of the present invention, in step (3), drying is performed at 130° C. to 150° C. for 3 to 5 minutes until a semi-cured layer is formed on the bottom layer.
[0071] In a preferred embodiment of the present invention, in step (3), drying is performed at 150° C. for 1 to 3 hours until the surface layer is completely solidified.
[0072] All raw materials used in the examples of the present invention are commercially available.
[0073] The technical solution of the present invention is further illustrated by the following embodiments.
[0074] Example 1
[0075] (1) Carbon steel U75V was polished with SiC sandpaper of 100, 400, 600, 800, 1000, and 1500 meshes in sequence. After polishing, it was ultrasonically cleaned in deionized water, anhydrous ethanol, and acetone for 15 min in sequence. The obtained sample was recorded as P-U75V;
[0076] (2) 0.2 g of nanocellulose, 30 mL of ethanol, and 10 mL of ammonia water were mixed at 30 ° C (water bath) and magnetically stirred for 1 h, which was recorded as solution A. 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin, 0.1 g of γ-aminopropyltriethoxysilane (silane coupling agent KH550), and 0.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added to 10 mL of anhydrous ethanol and magnetically stirred for 1 h at 30 ° C, which was recorded as solution B. Solution A was poured into solution B and magnetically stirred at 30 ° C (water bath) for 1 h to obtain a primer;
[0077] 0.4 g of nanocellulose, 0.2 g of nano ZrO2, 0.1 g of nano SiO2, 30 mL of ethanol, and 10 mL of ammonia water were mixed at 30 ° C (water bath) and magnetically stirred for 30 min. Then 0.6 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was magnetically stirred at 30°C (water bath) for 30 min to obtain a hydrophobically modified micro-nanostructure particle emulsion, which was recorded as solution C. 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin, and 0.1 g of γ-aminopropyltriethoxysilane (silane coupling agent KH550) were added to 10 mL of anhydrous ethanol and magnetically stirred at 30°C for 30 min, and then 0.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added and magnetically stirred at 30°C (water bath) for 30 min, which was recorded as solution D. Solution C was poured into solution D and magnetically stirred at 30°C for 1 h to obtain a surface coating.
[0078] (3) First, the primer prepared by spraying the surface of P-U75V obtained in step (1) was dried at 130°C for 3 min to wait for the primer to form a semi-cured surface (denoted as P-U75V-F), and then the surface coating prepared by spraying was applied on the semi-cured surface, and finally, the coating was cured in a drying oven at 150°C for 1 h, and dried until the surface was completely cured to obtain a super hydrophobic coating with excellent mechanical properties, denoted as P-U75V-FS-1. The spraying flow rate of the spray gun was 0.1 mL / s, and the spray gun was sprayed at a distance of 20 cm from the substrate. The spray gun pressure was 0.2 MPa, and the spray gun moving speed was 2 cm / s.
[0079] Example 2 (the mass ratio of the micro-nano structure particles in the bottom layer to the hydrophobically modified micro-nano structure particles in the surface layer is 0.6:1)
[0080] (1) Carbon steel U75V was polished with SiC sandpaper of 100, 400, 600, 800, 1000, and 1500 meshes in sequence. After polishing, it was ultrasonically cleaned in deionized water, anhydrous ethanol, and acetone for 15 min in sequence. The obtained sample was recorded as P-U75V;
[0081] (2) 0.6 g of nanocellulose, 30 mL of ethanol, and 10 mL of ammonia water were mixed and magnetically stirred at 30 ° C for 1 h, which was recorded as solution A. 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin, 0.1 g of γ-aminopropyltriethoxysilane (silane coupling agent KH550), and 0.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added to 10 mL of anhydrous ethanol and magnetically stirred at 30 ° C for 1 h, which was recorded as solution B. Solution A was poured into solution B and magnetically stirred at 30 ° C for 2 h to obtain a primer;
[0082] 0.5 g of nanocellulose, 0.3 g of nano ZrO2, 0.2 g of nano SiO2, 30 mL of ethanol and 10 mL of ammonia water were mixed and magnetically stirred at 30°C for 30 min, and then 0.6 g of 1H,1H,2H,2H-perfluorodecyl triethoxysilane was added and magnetically stirred at 30°C for 30 min to obtain a hydrophobically modified micro-nano structure particle emulsion, which was recorded as solution C. 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin and 0.1 g of silane coupling agent were added to 10 mL of anhydrous ethanol and magnetically stirred at 30°C for 30 min, and then 0.3 g of 1H,1H,2H,2H-perfluorodecyl triethoxysilane was added and magnetically stirred at 30°C for 30 min, which was recorded as solution D. Solution C was poured into solution D and magnetically stirred at 30°C for 1 h to obtain a surface coating.
[0083] (3) First, the base coating prepared by spraying the surface of P-U75V obtained in step (1) was dried at 130°C for 3 min to wait for the base coating to form a semi-cured surface, and then the surface coating prepared by spraying was applied on the semi-cured surface, and finally, the coating was cured in a drying oven at 160°C for 1 h, and dried until the surface was completely cured to obtain a super hydrophobic coating with excellent mechanical properties (denoted as P-U75V-FS-2). The spraying flow rate of the spray gun was 0.1 mL / s, and the spray gun was fixed at a distance of 30 cm from the substrate for spraying. The spray gun pressure was 0.2 MPa, and the spray gun moving speed was 2 cm / s.
[0084] Example 3 (the mass ratio of the micro-nano structure particles in the bottom layer to the hydrophobically modified micro-nano structure particles in the surface layer is 0.2:1)
[0085] (1) Carbon steel U75V was polished with SiC sandpaper of 100, 400, 600, 800, 1000, and 1500 meshes in sequence. After polishing, it was ultrasonically cleaned in deionized water, anhydrous ethanol, and acetone for 15 min in sequence. The obtained sample was recorded as P-U75V;
[0086] (2) 0.2 g of nanocellulose, 30 mL of ethanol, and 10 mL of ammonia water were mixed and magnetically stirred at 30 ° C for 1 h, which was recorded as solution A. 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin, 0.1 g of γ-aminopropyltriethoxysilane (silane coupling agent KH550), and 0.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added to 10 mL of anhydrous ethanol and magnetically stirred at 30 ° C for 1 h, which was recorded as solution B. Solution A was poured into solution B and magnetically stirred at 30 ° C for 1 h to obtain a primer;
[0087] 0.5 g of nanocellulose, 0.3 g of nano ZrO2, 0.2 g of nano SiO2, 30 mL of ethanol and 10 mL of ammonia water were mixed and magnetically stirred at 30°C for 30 min, and then 0.6 g of 1H,1H,2H,2H-perfluorodecyl triethoxysilane was added and magnetically stirred at 30°C for 30 min to obtain a hydrophobically modified micro-nano structure particle emulsion, which was recorded as solution C. 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin and 0.1 g of silane coupling agent were added to 10 mL of anhydrous ethanol and magnetically stirred at 30°C for 30 min, and then 0.3 g of 1H,1H,2H,2H-perfluorodecyl triethoxysilane was added and magnetically stirred at 30°C for 30 min, which was recorded as solution D. Solution C was poured into solution D and magnetically stirred at 30°C for 1 h to obtain a surface coating.
[0088] (3) First, the primer coating prepared by spraying the surface of P-U75V obtained in step (1) was dried at 150° C. for 3 min to wait for the primer coating to form a semi-cured surface, and then the surface coating prepared by spraying was applied on the semi-cured surface, and finally, the coating was cured in a 150° C. drying oven for 1 h, and dried until the surface was completely cured to obtain a super hydrophobic coating with excellent mechanical properties (denoted as P-U75V-FS-3). The spraying flow rate of the spray gun was 1 mL / s, and the spray gun was fixed at a distance of 10 cm from the substrate for spraying. The spray gun pressure was 1 MPa and the spray gun moving speed was 2 cm / s.
[0089] Performance Testing
[0090] The schematic diagram of the preparation process of P-U75V-FS-1 in Example 1 of the present invention is shown in Figure 2 (a) in step (2), the hydrophobic modification principle of the hydrophobically modified micro-nanostructure particles is shown in Figure 2 (b) in .
[0091] The scanning electron microscope (SEM) image of P-U75V-FS-1 prepared in Example 1 of the present invention is shown in Figure 3 It can be seen that the coating surface exhibits a complex micro-nano multi-scale structure, with an overall porous structure, and many irregular nano-spherical structures are scattered on the pore walls, each of which is composed of nanoparticles. These complex structures provide a large number of "air pockets" when the surface contacts the liquid, which can block the liquid from invading the coating surface, and the multi-scale micro-nano structure can increase the contact angle of the super-hydrophobic coating. After mechanical friction, even if the nanoparticles on the surface are smoothed, there are still other scales of micro-nano structures that can maintain the super-hydrophobicity of the coating.
[0092] The static contact angle diagram of the water droplet and the surface of the super hydrophobic coating prepared in Examples 1-3 of the present invention is shown in Figure 4It can be seen that the static contact angles (WCA) of water droplets on the carbon steel surfaces after spray coating in Examples 1-3 are 166.5° (the test water droplet is 4 μL), 165.3° (the test water droplet is 4 μL) and (WCA) are 165° (the test water droplet is 4 μL), respectively, indicating that super-hydrophobic surface properties have been obtained.
[0093] The super-hydrophobic coating prepared in Examples 1-3 was subjected to a surface coating wear test. Under the condition of bearing a weight of 200 g, it was rubbed 130 times with 1000-mesh sandpaper (each friction distance was 20 cm). The static contact angle diagram of the water droplet and the surface is shown in FIG. Figure 5 It can be seen that the static contact angle value of the water droplet in Example 1 is reduced to 151.1°, the static contact angle value of the water droplet in Example 2 is reduced to 150.5°, and the static contact angle value of the water droplet in Example 3 is reduced to 151.5°, indicating that the super-hydrophobic coatings prepared in Examples 1-3 of the present invention have good mechanical properties.
[0094] The super-hydrophobic coatings prepared in Examples 1-3 and the untreated carbon steel U75V in Example 1 were subjected to electrochemical tests. The test solution was a 3.5% NaCl solution. The Tafel curves of the two are shown in FIG. Figure 6 It can be seen that the self-corrosion current density of the super-hydrophobic coating after coating in Example 1 is 4.339×10 -8 A / cm 2 The self-corrosion current density of Example 2 is 1.046×10 -8 A / cm 2 The self-corrosion current density of Example 3 is 8.757×10 -9 A / cm 2 , while the self-corrosion current density of untreated carbon steel U75V is 8.657×10 -7 A / cm 2 The self-corrosion current density of the super-hydrophobic coating prepared in Examples 1-3 of the present invention is lower than that of the substrate (untreated carbon steel U75V), which proves that the super-hydrophobic coating of the present invention has good corrosion resistance.
[0095] Comparative Example 1
[0096] (1) Carbon steel U75V was polished with SiC sandpaper of 100, 400, 600, 800, 1000, and 1500 meshes in sequence. After polishing, it was ultrasonically cleaned in deionized water, anhydrous ethanol, and acetone for 15 min in sequence. The obtained sample was recorded as P-U75V;
[0097] (2) 0.4 g of nanocellulose, 0.2 g of nano ZrO2, 0.1 g of nano SiO2, 30 mL of ethanol and 10 mL of ammonia water were mixed and magnetically stirred at 30 ° C for 30 min, and then 0.6 g of 1H, 1H, 2H, 2H-perfluorodecyl triethoxy silane was added and magnetically stirred at 30 ° C for 30 min to obtain a hydrophobically modified micro-nano structure particle emulsion, which was recorded as solution C. 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin and 0.1 g of γ-aminopropyl triethoxy silane (silane coupling agent KH550) were added to 10 mL of anhydrous ethanol and magnetically stirred at 30 ° C for 30 min. Then 0.3 g of 1H, 1H, 2H, 2H-perfluorodecyl triethoxy silane was added and magnetically stirred at 30 ° C for 30 min, which was recorded as solution D. Solution C was poured into solution D and magnetically stirred at 30 ° C for 1 hour to obtain a coating.
[0098] (3) The coating prepared by spraying the P-U75V surface obtained in step (1) was first placed in a 150° C. drying oven for curing for 1 h, and dried until the surface was completely cured to obtain a super hydrophobic coating. The spraying flow rate of the spray gun was 0.1 mL / s, and the spray gun was sprayed at a distance of 20 cm from the substrate. The spray gun pressure was 0.2 MPa and the spray gun moving speed was 2 cm / s.
[0099] Comparative Example 2
[0100] (1) Carbon steel U75V was polished with SiC sandpaper of 100, 400, 600, 800, 1000, and 1500 meshes in sequence. After polishing, it was ultrasonically cleaned in deionized water, anhydrous ethanol, and acetone for 15 min in sequence. The obtained sample was recorded as P-U75V;
[0101] (2) 0.2 g of nanocellulose, 30 mL of ethanol, and 10 mL of ammonia water were mixed and magnetically stirred at 30 ° C for 1 h, which was recorded as solution A. 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin, 0.1 g of γ-aminopropyltriethoxysilane (silane coupling agent KH550), and 0.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added to 10 mL of anhydrous ethanol and magnetically stirred at 30 ° C for 1 h, which was recorded as solution B. Solution A was poured into solution B and magnetically stirred at 30 ° C for 1 h to obtain a coating;
[0102] (3) The coating prepared by spraying the P-U75V surface obtained in step (1) was first dried at 130° C. for 3 min to wait for the bottom coating to form a semi-cured surface, and then placed in a 150° C. drying oven for 1 h, and dried until the surface was completely cured to obtain a super-hydrophobic coating. The spraying flow rate of the spray gun was 0.1 mL / s, and the spray gun was sprayed at a distance of 20 cm from the substrate. The spray gun pressure was 0.2 MPa and the spray gun moving speed was 2 cm / s.
[0103] Comparative Example 3
[0104] The same as Example 1, except that the surface coating was prepared by the following method: 0.2 g of nanocellulose, 30 mL of ethanol, and 10 mL of ammonia water were mixed and magnetically stirred at 30° C. for 1 h, recorded as solution A; 0.5 g of boron-modified phenolic resin, 1.5 g of phenolic resin, 0.1 g of γ-aminopropyltriethoxysilane (silane coupling agent KH550), and 0.3 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane were added to 10 mL of anhydrous ethanol and magnetically stirred at 30° C. for 1 h, recorded as solution B; solution A was poured into solution B, and magnetically stirred at 30° C. for 1 h to obtain a surface coating;
[0105] The remaining steps and dosages are the same as those in Example 1.
[0106] Performance Testing
[0107] The static contact angle diagrams of the water droplets and the surface of the coatings prepared in Comparative Examples 1-3 of the present invention are shown in Figure 7 , it can be seen that the static contact angle (WCA) of water droplets on the carbon steel surface after spray coating of comparative examples 1-3 is 165.2° (test water droplet is 4μL), 97° (test water droplet is 4μL) and (WCA) is 107° (test water droplet is 4μL), only comparative example 1 has super-hydrophobic effect. Further, the super-hydrophobic coating prepared in comparative example 1 is subjected to surface coating wear test, and under the condition of bearing 200g weight, after 1000 mesh sandpaper cyclic friction (each friction distance is 20cm), after cyclic friction 10 times, the contact angle is reduced to 146.2°, indicating that the super-hydrophobic coating prepared in comparative example 1 of the present invention has super-hydrophobic effect, but the ability to resist mechanical wear is low, and the mechanical properties are not stable.
[0108] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A super hydrophobic coating with excellent mechanical properties, characterized in that: It comprises a bottom layer and a surface layer arranged in sequence from bottom to top, wherein the raw materials of the bottom layer comprise fluorinated boron modified phenolic resin, phenolic resin and micro-nano structure particles, and the raw materials of the surface layer comprise fluorinated boron modified phenolic resin, phenolic resin and hydrophobically modified micro-nano structure particles; The mass ratio of the micro-nano structure particles in the bottom layer to the hydrophobically modified micro-nano structure particles in the surface layer is (0.2-0.6):
1.
2. A method for preparing a super-hydrophobic coating with excellent mechanical properties as claimed in claim 1, characterized in that: The following steps are involved: A layered spraying method is adopted to spray a bottom layer coating and a top layer coating on the surface of the substrate in sequence, and after drying and curing, a bottom layer and a top layer are formed in sequence on the surface of the substrate to obtain the super hydrophobic coating with excellent mechanical properties; The primer is prepared by using a fluorine-containing boronized modified phenolic resin and a phenolic resin mixture as the main body, embedding micro-nano structure particles, and dispersing them in a solvent; The surface coating is prepared by taking fluorine-containing boronized modified phenolic resin and a phenolic resin mixture as the main body, embedding hydrophobic modified micro-nano structure particles, and dispersing them in a solvent.
3. The preparation method of the super-hydrophobic coating with excellent mechanical properties according to claim 2, characterized in that, In the primer, the micro-nano structure particles include one or more of hydroxylated multi-walled carbon nanotubes and nanocellulose; the mass ratio of the fluorine-containing boron-modified phenolic resin to the phenolic resin is 1: (2.5-3.5); the mass ratio of the micro-nano structure particles to the fluorine-containing boron-modified phenolic resin is 2:
5.
4. The preparation method of the super-hydrophobic coating with excellent mechanical properties according to claim 2, characterized in that, In the surface coating, the hydrophobically modified micro-nano structure particles include one or more of ZrO2, SiO2, Al2O3, TiO2, hydroxylated multi-walled carbon nanotubes, nanocellulose, Fe3O4, Fe2O3 and ZnO modified with fluorine-containing siloxane; the mass ratio of the fluorine-containing boron-modified phenolic resin to the phenolic resin is 1: (2.5-3.5), and the mass ratio of the hydrophobically modified micro-nano structure particles to the fluorine-containing boron-modified phenolic resin is 7:
5.
5. The preparation method of the super-hydrophobic coating with excellent mechanical properties according to claim 2, characterized in that, The specific steps include: (1) grinding, polishing and ultrasonic cleaning the substrate surface; (2) dispersing the fluorine-containing boron-modified phenolic resin, phenolic resin, and micro-nano structure material in a solvent, heating and stirring in a water bath to obtain a base coating; dispersing the fluorine-containing boron-modified phenolic resin, phenolic resin, and hydrophobic modified micro-nano structure material in a solvent, heating and stirring in a water bath to obtain a surface coating; (3) first spraying the base coating on the surface of the substrate obtained in step (1), drying until the base coating forms a semi-cured layer, then spraying the top coating, and continuing to dry until the top coating is completely cured to obtain the super hydrophobic coating with excellent mechanical properties.
6. The method for preparing a super-hydrophobic coating with excellent mechanical properties according to claim 5, wherein: In step (2), the temperature of the water bath heating and stirring is 30° C., and the time is 0.5 to 3 h.
7. The method for preparing a super-hydrophobic coating with excellent mechanical properties according to claim 5, wherein: In step (3), the spraying flow rate of the spray gun is 0.1-1 mL / s, the spray gun sprays at a distance of 10-30 cm from the substrate, the spray gun pressure is 0.2-1 MPa, and the spray gun movement speed is 2 cm / s.
8. The method for preparing a super-hydrophobic coating with excellent mechanical properties according to claim 5, wherein: In step (3), drying is performed at 130° C. to 150° C. for 3 to 5 minutes until a semi-cured layer is formed on the bottom layer.
9. The method for preparing a super-hydrophobic coating with excellent mechanical properties according to claim 5, wherein: In step (3), drying is performed at 150° C. for 1 to 3 hours until the surface layer is completely solidified.
Citation Information
Patent Citations
Photocatalytic type self-repairing super-hydrophobic coating and preparation method thereof
CN103409028A
Structural coatings with dewetting and anti-icing properties, and processes for fabricating these coatings
CN105121589A
Preparation method of super-hydrophobic composite coating capable of preventing icing for long time and method for recovering anti-icing property of super-hydrophobic composite coating
CN115304965A
Hydrophobically modified thermosetting phenolic resin, aerogel and aerogel-based composite material
CN115417958A
Flame-retardant super-amphiphobic metal slow-release anticorrosive coating material and preparation method thereof
CN118027781A